Influence of the substrate material on the optical properties of tungsten diselenide monolayers. (9th March 2017) - Lippert, Sina; Schneider, Lorenz Maximilian; Renaud, Dylan; Kang, Kyung Nam; Ajayi, Obafunso; Kuhnert, Jan; Halbich, Marc-Uwe; Abdulmunem, Oday M; Lin, Xing; Hassoon, Khaleel; Edalati-Boostan, Saeideh; Kim, Young Duck; et al.
Abstract: Monolayers of transition-metal dichalcogenides such as WSe2 have become increasingly attractive due to their potential in electrical and optical applications. Because the properties of these 2D systems are known to be affected by their surroundings, we report how the choice of the substrate material affects the optical properties of monolayer WSe2 . To accomplish this study, pump-density-dependent micro-photoluminescence measurements are performed with time-integrating and time-resolving acquisition techniques. Spectral information and power-dependent mode intensities are compared at 290 K and 10 K for exfoliated WSe2 on SiO2 /Si, sapphire (Al2 O3 ), hBN/Si3 N4 /Si, and MgF2, indicating substrate-dependent appearance and strength of exciton, trion, and biexciton modes. Additionally, one CVD-grown WSe2 monolayer on sapphire is included in this study for direct comparison with its exfoliated counterpart. Time-resolved micro-photoluminescence shows how radiative decay times strongly differ for different substrate materials. Our data indicates exciton–exciton annihilation as a shortening mechanism at room temperature, and subtle trends in the decay rates in correlation to the dielectric environment at cryogenic temperatures. On the measureable time scales, trends are also related to the extent of the respective 2D-excitonic modes' appearance. This result highlights the importance of further detailed characterization of exciton features in 2D materials, particularly with respect to the choice of substrate.